Clinical characterization of patients undergoing septoplasty by Cottle technique. Hospital General Universitario Dr. Luis Gómez López (Boletin Médico de Postgrado, 2024)
The present investigation was carried out with the objective of clinically characterizing patients who underwent septoplasty with the Cottle technique at the Otorhinolaryngology Service of the Hospital General Universitario Dr. Luis Gómez López in the period January 2022 - April 2023. 37% of the patients had an age range between 46 and 66 years old. Seventy-eight percent of the patients were male. 65% presented space-occupying lesions in the nostrils and 22% showed suspected granulomatous disease. As for histopathological diagnoses, most patients presented nasal polyps (30%) and nasal papillomatosis (21%). In 7% of the patients the parasitological study detected Leishmaniasis and in 4% mucormycosis while in 4% of the patients the nasal secretion culture was positive for Klebsiella rhinoscleromatis.